Comparison of Topical and Subconjunctival Curcumin Injection on Corneal Neovascularization on Alkali Injuries of Wistar’s Cornea. - Rakhmasari Y.A; Sri Inakawati; Siti Sundari; Winarto Winarto; Ediati Sasmito (Majalah Oftalmologi Indonesia, 2015)
Background: Neovascularization of the cornea causing loss of corneal clarity, decrease of visual acuity and also improve the failure of Keratoplasty. It can occur due to the imbalance of angiogenic and antiangiogenic factors such as on chemical trauma. Curcumin is the active extract which have anti-angiogenesis pharmacological effect. Subconjungtival injection have many advantages compared with topical administration. The purpose is to compare the effect of subconjunctival curcumin injection and topical curcumin on corneal neovascularization on alkali injuries of wistar’s cornea. Methods: Experimental study with post test only control group design using 28 male Wistar rat strain which received chemical trauma. The samples were randomly devided into 4 group. Topical curcumin 80 μmol/L, topical DMSO 0,1% five times daily for 7 days. Subconjunctival injection of curcumin 40 μmol/L and DMSO 0,1% were received once after the chemical trauma on the cornea. On day 8 was measured the corneal neovascularization in length of blood vessels and width of area. Statisticaly hypotheses with independent t-test and significant p < 0,05. Result: Subconjunctival injection of curcumin group were significantly reduced the area of corneal neovascularization than topical curcumin group (p = 0,045). Conclusion: Subconjunctival injection of curcumin needs further study to compare the benefits and side effect